2021
DOI: 10.1186/s12889-021-11467-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and wellbeing coordinators in primary schools to support student mental health: protocol for a quasi-experimental cluster study

Abstract: Background Half of mental health disorders begin before the age of 14, highlighting the importance of prevention and early-intervention in childhood. Schools have been identified globally by policymakers as a platform to support good child mental health; however, the majority of the research is focused on secondary schools, with primary schools receiving very little attention by comparison. The limited available evidence on mental health initiatives in primary schools is hindered by a lack of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
8
0
4
Order By: Relevance
“…Upaya promotif dan preventif terkait kesehatan jiwa di sekolah yang telah dilakukan berupa deteksi dini kesehatan jiwa bagi siswa/peserta didik menggunakan SDQ; pelatihan kader SEHATI; dan berkolaborasi dengan Puskesmas maupun sekolah untuk sosialisasi dan promosi kesehatan jiwa. Pelatihan kader sekolah sehat jiwa (SEHATI) di sekolah merupakan bentuk dari upaya promotif dan preventif mengingat bahwa sekolah berkontribusi dalam mendukung kesejahteraan dan kesehatan mental semua siswa untuk mengidentifikasi dan mengelola siswa dengan masalah kesehatan mental yang muncul sejak dini, serta menargetkan intervensi pada siswa dengan masalah kesehatan jiwa yang signifikan (Darling et al, 2021).…”
Section: Pembahasanunclassified
“…Upaya promotif dan preventif terkait kesehatan jiwa di sekolah yang telah dilakukan berupa deteksi dini kesehatan jiwa bagi siswa/peserta didik menggunakan SDQ; pelatihan kader SEHATI; dan berkolaborasi dengan Puskesmas maupun sekolah untuk sosialisasi dan promosi kesehatan jiwa. Pelatihan kader sekolah sehat jiwa (SEHATI) di sekolah merupakan bentuk dari upaya promotif dan preventif mengingat bahwa sekolah berkontribusi dalam mendukung kesejahteraan dan kesehatan mental semua siswa untuk mengidentifikasi dan mengelola siswa dengan masalah kesehatan mental yang muncul sejak dini, serta menargetkan intervensi pada siswa dengan masalah kesehatan jiwa yang signifikan (Darling et al, 2021).…”
Section: Pembahasanunclassified
“…Due to the specific demographics of the participants in the research study, ages eight to eighteen and having EPP, research on children's mental health and the impact of having a disability on mental health were both explored to further the body of knowledge. Before the age of fourteen, about half of mental health conditions have begun (Darling et al, 2021). This means that prevention of mental illnesses is very important in the youth community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The events that occur in childhood could contribute to the development of mental health conditions that begin before the age of fourteen. About 10-17% of children and young adults ages four to seventeen qualify for the definition of a mental illness (Darling et al, 2021). Mental health conditions, when left alone or ignored in childhood, could short-term affect children's performance in school and long-term lead to more serious and dangerous events such as suicide and low life quality as an adult (Darling et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike junior high school students, high school students faced many new challenges, including adjusting to a new environment, making new friends, academic challenges, and National College Entrance Examination (NCEE), which makes them more vulnerable to MHP. Studies have shown that half of MHP begin by the age of 14, and most cases go undetected and untreated [ 4 ]. In addition, according to the “Report on National Mental Health Development in China (2019–2020)”, the detection rate of depression in primary school is about 10%, while that in high schools reaches 40%.…”
Section: Introductionmentioning
confidence: 99%